Małżeństwa vs związki nieformalne w opiniach młodych mieszkańców Łodzi - Anna Janiszewska (Space, Society, Economy, 2013)
In this article, I present the opinions of young inhabitants of Łódź regarding marriage and civil partnerships in the context of matrimonial behaviour of the inhabitants of Łódź. I complemented the analysis of statistical material with a survey study. I selected surveyees on purpose to acquire the opinions of people entering the stage in their lives related to matrimonial behaviours. The choice to conduct the study on the inhabitants of a city with the third largest population in Poland was also intentional. This was supported by the values of the indicators of demographic transformations which confirmed the growing changes in Łódź since the beginning of the Polish transformation in the 1980s. The results indicate that young inhabitants of Łódź display openness towards new demographic phenomena, but, in some aspects, they support traditional values. Undeniably, the surveyees are three times more likely to permit cohabitating relationships than to dismiss them. At the same time, they treat their current informal relationships as trial relationships rather than a way of living in the future. They mostly declare they want to enter into marriage rather than into informal relationships. This indicates that marriage as an institution is not threatened by cohabitating relationships even though the scope of the phenomenon will increase.